2019
DOI: 10.1177/1559827619883603
|View full text |Cite
|
Sign up to set email alerts
|

The Mismatch of Nutrition and Lifestyle Beliefs and Actions Among Physicians: A Wake-Up Call

Abstract: Background. There is a notable lack of education on nutrition and physical activity guidelines in medical schools and postgraduate training. The purpose of this study is to assess the nutrition and exercise knowledge and personal health behaviors of physicians in the Department of Medicine at a large academic center. Methods. We conducted a survey study in the Department of Medicine at the University of Florida in 2018. The survey instrument included questions on demographics, medical comorbidities, baseline p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 54 publications
1
29
0
Order By: Relevance
“…Is it okay that no clinician thought to help this patient through dietary and lifestyle changes (directly or indirectly by referring them to an RD)? Dr. Barnard and I would both argue that this is no longer acceptable even though the majority of clinicians report poor or no nutrition training [ 6 , 8 , 13 , 14 ]—61% in one survey of internal medicine residents [ 15 ]. A multinational systematic review of qualitative and quantitative studies concluded that nutrition is poorly incorporated into medical education at best no matter the location or student seniority despite student desire for nutrition education [ 16 ].…”
Section: Nutrition Education and Health Carementioning
confidence: 99%
See 2 more Smart Citations
“…Is it okay that no clinician thought to help this patient through dietary and lifestyle changes (directly or indirectly by referring them to an RD)? Dr. Barnard and I would both argue that this is no longer acceptable even though the majority of clinicians report poor or no nutrition training [ 6 , 8 , 13 , 14 ]—61% in one survey of internal medicine residents [ 15 ]. A multinational systematic review of qualitative and quantitative studies concluded that nutrition is poorly incorporated into medical education at best no matter the location or student seniority despite student desire for nutrition education [ 16 ].…”
Section: Nutrition Education and Health Carementioning
confidence: 99%
“…Further, the literature shows that the understandings health care providers have currently may be inaccurate. In a 2018 survey of University of Florida physicians (92%), only 25% knew the American Heart Association recommendation for vegetable and fruit intake while 46% knew the recommendation for physical activity [ 14 ]. While neither statistic is comforting, the meager 1 in 4 practicing physicians with such fundamental nutrition knowledge is alarming.…”
Section: Nutrition Education and Health Carementioning
confidence: 99%
See 1 more Smart Citation
“…3 Similarly, physicians in multiple settings report agreement that eating well and being physically active are beneficial to personal health, but less than 25% reported actually engaging in these activities. 10 Finally, although smoking in health care settings has dramatically decreased since the 1970s, 25% of licensed practical nurses still smoke. 11 Often, nurses begin smoking prior to starting their job and, consistent with the general population, have trouble quitting.…”
Section: Behaviors That Increase Health Riskmentioning
confidence: 99%
“…While healthcare providers are more engaged in healthy lifestyle behaviors compared to the general public, they lack the education and training in these areas. The authors call for improved medical education in the areas of nutrition and physical activity [8].…”
Section: Studies Measuring Wellness In Healthcare Providersmentioning
confidence: 99%